The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10040-020-02145-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeological evaluation of managed aquifer recharge in a glacial moraine complex using long-term groundwater data analysis

Abstract: Managed aquifer recharge (MAR) is a strategy to address dwindling water availability that is used to recharge stressed groundwater systems for recovery or adaptation purposes. Glacial moraine complexes can host large groundwater volumes in thick coarse-grained sandy and gravelous aquifers, and therefore are often suitable for MAR. In this research, the impact of 20 years of MAR (infiltration) in the Veluwe glacial moraine complex in the Netherlands is evaluated through time-series analysis and water quality mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…They concluded that practitioners could use DPSIR for local-scale studies because it assesses the place-specific nuances of multiple concerned stakeholders more realistically. In Van Noordwijk et al (2020), DPSIR was used to understand the joint multiscale phenomena in the forest-water-people nexus and, thus, diagnosed issues to be addressed in local decision-making. Therefore, DPSIR was considered an appropriate framework for meeting the aim of the research.…”
Section: Case Analysis Methodsmentioning
confidence: 99%
“…They concluded that practitioners could use DPSIR for local-scale studies because it assesses the place-specific nuances of multiple concerned stakeholders more realistically. In Van Noordwijk et al (2020), DPSIR was used to understand the joint multiscale phenomena in the forest-water-people nexus and, thus, diagnosed issues to be addressed in local decision-making. Therefore, DPSIR was considered an appropriate framework for meeting the aim of the research.…”
Section: Case Analysis Methodsmentioning
confidence: 99%
“…However, some of the Veluwe abstractions affect valuable groundwaterdependent ecosystems nearby as well as historical brooks and springs on the Veluwe's periphery. Various measures have been proposed or implemented to compensate for these impacts , Van Engelenburg et al, 2020.…”
Section: Drinking Water Abstraction In the Veluwe Area In The Netherlmentioning
confidence: 99%
“…A model is considered valid with an explained variance percentage (EVP) > 70%, an evaporation factor between 0.5 and 1.5, and the root mean squared error (RMSE) smaller than 0.15. An overview of the Menyanthes results for all 101 time series is available in ESM1, electronic supplementary material to VanEngelenburg et al (2020). Valid models with explanatory series P (precipitation) and E (evaporation).…”
mentioning
confidence: 99%